A Survey of Women Entrepreneurs in Malaysia: A Case of Siti Khadijah Market, Kelantan and Pekan Rabu, Kedah (Journal of Governance and Development (JGD), 2015)
Efforts taken by Malaysian government to encourage her people to venture into business are undeniable. As women constitute nearly half of the total population, women’s contribution towards national economic development has been recognized by Malaysian government. Women have to compete together with men in order to ensure that their status within the society is uplifted. Their involvement as business entrepreneurs make them at par with other successful male counterparts. This paper is to look at women entrepreneurs at both Siti Khadijah Market, Kelantan and Pekan Rabu, Kedah. Data were based on research done to both places. The findings of the research show that strong competition has been identified as the most challenge those women faced as an entrepreneur. Besides, assisting family total income is the most influencing factor that lead them to become entrepreneurs and acquiring appropriate skills as entrepreneur is also has been identified will further improve on their way of doing business.